An unexpected pathogen causing multiple intra-abdominal abscesses in an immunocompetent patient - Felipe Vera-Polanía (Asociación Colombiana de Infectología, 2021)
Streptococcus constellatus is a member of the group now called Streptococcus anginosus. This microorganism is part of the normal oropharyngeal, gastrointestinal and genitourinary microbiota. However, it may cause serious infections such as pharyngitis, bacteremia and invasive pyogenic infections in immunocompromised patients. We report the first case in Colombia of an adult male with no relevant medical history and with an unusual presentation of infection by S. constellatusand whose laboratory results showed an important systemic inflammatory response and radiographic evidence of abdominal involvement with poor response to medical and surgical management. Since there are few reports in international medical journals about intra-abdominal infection by S. constellatus and taking into consideration the need of a multidisciplinary intervention, this report may be of interest for both clinical and surgical practitioners.